Efektivitas Fungsi Pengawasan Bbpom Dalam Izin Edar Terhadap Obat-Obatan Penyebab Problematika Gagal Ginjal Akut Pada Anak-Anak Di Kota Mataram NTB - Luhulima, Muh.Al-Fayyadh; H. Arba, H. Arba (Private Law, 2024)
This study aims to determine the effectiveness of the supervisory function of BBPOM Mataram in supervising drugs that cause problematic acute kidney failure in children in the city of Mataram, NTB, and to find out the legal efforts made by BBPOM Mataram so that they can be optimal in protecting the public against drugs that cause problems of acute renal failure in children. The type of research used is empirical research, with statutory, conceptual, and sociological approaches. The results of the research and discussion show that the effectiveness of the supervisory function of BBPOM is less effective, even though they have carried out supervision by conducting raids and inspections, these activities should be carried out routinely and in carrying out socialization or counseling there are no activities that are more specific to the problem of drugs containing ethylene glycol and diethylene. Glycol (a dangerous chemical) causes acute kidney failure and lack of socialization through social media. BBPOM Mataram did not take legal action because, in the city of Mataram, no factories that produced drugs. Hence, they only gave administrative sanctions to pharmaceutical facilities if they violated the provisions.